Expert consensus on the desirable characteristics of review criteria for improvement of health care quality. Issue 3 (1st September 2001) - Hearnshaw, H M; Harker, R M; Cheater, F M; Baker, R H; Grimshaw, G M
Abstract : Objectives —To identify the desirable characteristics of review criteria for quality improvement and to determine how they should be selected. Background —Review criteria are the elements against which quality of care is assessed in quality improvement. Use of inappropriate criteria may impair the effectiveness of quality improvement activities and resources may be wasted in activities that fail to facilitate improved care. Methods —A two round modified Delphi process was used to generate consensus amongst an international panel of 38 experts. A list of 40 characteristics of review criteria, identified from literature searches, was distributed to the experts who were asked to rate the importance and feasibility of each characteristic. Comments and suggestions for characteristics not included in the list were also invited. Results —The Delphi process refined a comprehensive literature based list of 40 desirable characteristics of review criteria into a more precise list of 26 items. The expert consensus view is that review criteria should be developed through a well documented process involving consideration of valid research evidence, possibly combined with expert opinion, prioritisation according to health outcomes and strength of evidence, and pilot testing. Review criteria should also be accompanied by full clear information on how they might be used and how data might be collected and interpreted. Conclusion —The desirable characteristics for review criteria have been identified and will be of use in the development, evaluation, and selection of review criteria, thus improving the cost effectiveness of quality improvement activities in healthcare settings.